THE DOMESTICATION EFFORT OF POTENTIAL CULTIVATION OF LOCAL ORNAMENTAL FISH GERMPLASM IN WATERS AROUND THE CAMPUS OF BANGKA BELITUNG UNIVERSITY - Robin Robin; Endang Bidayani; Eva Prasetiyono; Ahmad Fahrul Syarif; Denny Syaputra (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
The aims of this research were to inventorize fish species and their spatial distribution in river of UBB and to domesticate local fish of Bangka Island that have high economic value, especially those that live around the campus of Bangka Belitung University. This research have done on July to September 2019. Test material used in this study were fish and water from river in the campus of Bangka Belitung University. The research methods were survey methods and descriptive (sampling) methods. Data in this research were the form of fish and water quality. Data of fish included of length, body weight and sex with the size of sample fish separated by the length : seed fish (10-20 mm), juvenile fish (21-40 mm) and adult fish (41-50 mm). Data of water quality taken by observate the parameters, included of temperature, dissolved oxygen (DO), pH, turbidity, brightness, hardness, current speed, and water deep. Data of fish samples were analyzed by simple linear regression analysis method, while data of water quality parameter were analyzed descriptively